Pengaruh Woolwich Massage Terhadap Pengeluaran ASI pada Ibu Post Partum di Desa Sukoreno Prigen Kabupaten Pasuruan - Fauziyah, Rahma (NHM PRESS, 2024)
Breast milk is vital for newborns, yet many postpartum mothers encounter challenges in milk production, sometimes even facing complete milk absence. This can result from various factors, including nutrition, breast care, and psychological issues. Woolwich massage has been proposed as a method to enhance milk production.The study aims to evaluate the effect of Woolwich massage on breast milk production among postpartum mothers in Sukoreno Prigen, Pasuruan. A quantitative pre-experimental design was utilized, specifically a one-group pre-post test approach. The research focused on postpartum mothers who had been breastfeeding for one month, with a sample size of 30 respondents selected through total sampling.Results indicated that prior to the massage, 25 participants (83.3%) experienced relatively smooth milk production. After the intervention, 23 participants (76.7%) reported improved milk flow. Statistical analysis using the Wilcoxon test revealed a significant p-value of 0.000 (p < 0.05), leading to the rejection of the null hypothesis.These findings suggest that Woolwich massage positively influences breast milk production in postpartum mothers. The study emphasizes the importance of community awareness regarding breastfeeding and the benefits of Woolwich massage for facilitating smooth milk production.